2016
DOI: 10.5539/ijef.v8n4p23
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamic Linkages among Sector Indices: The Case of the Egyptian Stock Market

Abstract: The main thrust of this study is to investigate both the long-term and short-term links among sectors of the Egyptian equity market. The empirical analysis is carried out using Johansen's multivariate cointegration analysis and Granger's causality analysis. The investigation period extends from 3 April 2011 to 31 May 2015.The results of cointegration analysis indicate that there exists a single cointegrating vector within the sample sector indices. The Granger's causality analysis shows that the short-term cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 59 publications
(51 reference statements)
3
10
0
Order By: Relevance
“…Thus, the market authorities suspended trading for around eight weeks. Over the period extending from January 2011 to October 2015, the market capitalisation decreased by 18%, the Egyptian pound fell sharply by 34.3% against the US dollar, and net foreign reserves shrank by 52% (Ahmed, 2016(Ahmed, , 2017. In the beginning of 2007, the Egyptian Exchange (EGX) constructed for the first time 12 equity sector indexes to track the movements of equity prices .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the market authorities suspended trading for around eight weeks. Over the period extending from January 2011 to October 2015, the market capitalisation decreased by 18%, the Egyptian pound fell sharply by 34.3% against the US dollar, and net foreign reserves shrank by 52% (Ahmed, 2016(Ahmed, , 2017. In the beginning of 2007, the Egyptian Exchange (EGX) constructed for the first time 12 equity sector indexes to track the movements of equity prices .…”
Section: Introductionmentioning
confidence: 99%
“…They asserted that the banking sector was the most influential in the Greek economy, followed by the industrial sector. Ahmed (2016) also found that the banking index was the leading sector in the Egyptian stock market. Kouki et al (2011) analyzed emerging stock markets by using VAR, BEKK, CCC, and DCC-GARCH methods.…”
Section: Literature Reviewmentioning
confidence: 92%
“…The political instability occurred during and after the revolution affected the economic and financial climate negatively. All stock market indices experienced and the Egyptian participation steep declines due to the revolution outbreak and the political instability that the country had faced at that time (Ahmed, 2016). So, it was necessary to take precautionary measures to protect the market after re-opening.…”
Section: Smithmentioning
confidence: 99%